Orson Scott Card’s Speculative Fictions: Blending Science Fiction and Fantasy - Senior, W. A. (Hungarian Journal of English and American Studies, 2021)
A prolific author, Orson Scott Card has written works that encompass a range of genres including a large body of commentary, Mormon drama, science fiction, fantasy, and horror, and often melds elements of one into another. In particular, as John Clute notes, “a ‘feel’ of fantasy pervades much of his s[cience] f[iction] work.” In fictions such as Enders Game, Treason, and Wyrms, and stories like “The Originist,” his tribute to Asimov’s Second Foundation, he employs traditional elements of fantasy: its language in references to wizards, dragons, magic, and such characters as dwelfs, a portmanteau of “elf” and “dwarf”; the episodic quest narrative of escalating perils undertaken by the protagonist, who moves from isolation to community; and the conventional, often medieval, fantasyscape of fabulous forests, rivers, and mountains. Through such a strategy Card establishes a heightened significance to human experiences that both genres address, and opens another portal to the sense of wonder that informs each. (WAS)